Antecedents Of Customer Satisfaction And Repurchase Intention Use Financial Technology (Fintech) Go Pay In Medan City - Dewi Setia Tarigan, Eka; Khairunnisak, Khairunnisak; Sabrina, Hesti; Parulian, Tohap; Syahputri, Yuni (Publisher Cv. Inara, 2022)
The purpose of this study was to analyze the effect of perceived ease of use and trust on the customer satisfaction and repurchase intention of fintech go pay consumers in Medan city and determine the effect of customer satisfaction in mediating perceived ease of use and trust on the repurchase intention of fintech go pay in Medan city. This study use a samples was 100 respondents, which were taken proportionally from every area in Medan City, the sampling technique was carried out purposive. The analytical method used is partial least square through the software smartPLS3.